Generation Z in search of the future: the didactic-pedagogical model of TikTok Mundi (Altre Modernità, 2024)
This article presents the educational project TikTok Mundi, funded by the University of Milan, by focusing on its role in promoting digital citizenship among high school and university students. The project stands out for its innovative approach based on co-design and collaboration, aimed at developing critical skills in the use of digital media and fostering active participation in the production of audiovisual content. The analysis of the key components of TikTok Mundi—interactive workshops, training internships, and public events—demonstrates that these initiatives offered students a unique opportunity to explore and understand the cultural dynamics of contemporary digitization. In particular, the article discusses how the project enhanced the identities and talents of the participants, while encouraging a constructive dialogue between the university, local community, and educational institutions. Finally, the article emphasises the crucial importance of initiatives like TikTok Mundi in promoting active and informed citizenship, integrating interdisciplinary perspectives into future education, and enriching the educational landscape with an inclusive and innovative approach.
Keywords: didactic-pedagogical model; active citizenship; digital inclusion; school-university synergy; cross-media; empowerment